Antipsychotic polypharmacy in patients with schizophrenia: a multicentre comparative study in East Asia - Sim, Kang (Blackwell Science Inc, 2004)
AIMS: Previous studies of the prescription patterns of psychotropic medications in patients with schizophrenia have highlighted a high rate of antipsychotic polypharmacy, but data in Asia are sparse. This study seeks to examine the prevalence of antipsychotic polypharmacy in patients with schizophrenia and compare the differences between patients receiving one vs. those receiving more than one antipsychotic. METHODS: Antipsychotic prescription for a sample of 2399 patients with schizophrenia from six countries and territories was evaluated. Daily doses of antipsychotic medications were converted to standard chlorpromazine equivalents (CPZ). RESULTS: Antipsychotic polypharmacy was found in 45.7% (n = 1097) of the patients with wide intercountry variations. Polypharmacy was associated with male gender [odds ratio (OR) 1.24, 95% confidence interval (CI) 1.06, 1.46, P < 0.01], advanced age (t = −7.81, d.f. = 2396, P < 0.001), psychiatric hospital setting (OR 1.34, 95% CI 1.11, 1.62) as well as higher daily CPZeq doses (411.47 vs. 983.10 CPZeq day(−1), z = −25.94, P < 0.001), anticholinergic use (OR 3.17, 95% CI 2.65, 3.79, P < 0.001) and less use of an atypical antipsychotic drug (OR 0.83, 95% CI 0.71, 0.98, P < 0.05). On multivariate analysis, country, age and duration of illness were significantly associated with antipsychotic polypharmacy. CONCLUSION: This study highlighted the wide intercountry variations of antipsychotic polypharmacy which are likely to be influenced by a complex combination of clinical, setting, cultural and personal practice factors, requiring more research.